A Study on Factors Affecting Consumer Behavior toward Men’s Skin Care Products among Mellennials: A Malaysian Case Study - Li, Mengru (2014)
This study seeks to determine the factors affecting consumer behavior toward men’s skin care products among Generation Y, especially in Malaysia. Other than that, the study also aims to identify the factor that has the strongest influence and to examine whether there is a significant difference between race and the consumer behavior toward men’s skin care products. There are 4 factors that act as the independent variables in this study, which are beliefs (B), celebrity (C), social expectation (SE) and self-image (SI). In meantime, consumer behavior (CB) will be the lead role as dependent variable. To achieve this objective, quantitative approach will be used with questionnaire as a tool. Smart PLS software is utilized to run reliability, validity as well as hypothesis test in order to examine relationship among constructs. SPSS is also used in the study for examining whether there is significant difference between race and the consumer behavior toward men’s skin care products. The outcome of the study indicated four factors were all significant and celebrity has the strongest influence on consumer behavior. Besides, there is significant difference between race and consumer behavior toward men’s skin care products. This study provides men’s skin care product providers a perspective for developing marketing strategies to increase the sales of men’s skin care products.